A Reappraisal of GAT-1 Localization in Neocortex - Fattorini, Giorgia; Melone, Marcello; Conti, Fiorenzo (Frontiers in Cellular Neuroscience, 2020)
γ-Aminobutyric acid (GABA) transporter (GAT)-1, the major GABA transporter in the brain, plays a key role in modulating GABA signaling and is involved in the pathophysiology of several neuropsychiatric diseases, including epilepsy. The original description of GAT-1 as a neuronal transporter has guided the interpretation of the findings of all physiological, pharmacological, genetic, or clinical studies. However, evidence published in the past few years, some of which is briefly reviewed herein, does not seem to be consistent with a neurocentric view of GAT-1 function and calls for more detailed analysis of its localization. We therefore performed a thorough systematic assessment of GAT-1 localization in neocortex and subcortical white matter. In line with earlier work, we found that GAT-1 was robustly expressed in axon terminals forming symmetric synapses and in astrocytic processes, whereas its astrocytic expression was more diffuse than expected and, even more surprisingly, immature and mature oligodendrocytes and microglial cells also expressed the transporter. These data indicate that the era of “neuronal” and “glial” GABA transporters has finally come to a close and provide a wider perspective from which to view GABA-mediated physiological phenomena. In addition, given the well-known involvement of astrocytes, oligodendrocytes, and microglial cells in physiological as well as pathological conditions, the demonstration of functional GAT-1 in these cells is expected to provide greater insight into the phenomena occurring in the diseased brain as well as to prompt a reassessment of earlier findings.